Entre as esquinas da história do Brasil: uma análise da trajetória de adolescentes negros e as medidas socioeducativas de restrição e privação de liberdade - Vieira, Luana Rodrigues (My University, 2024)
The trajectory of black adolescents and socio-educational measures of restriction and deprivation of freedom is the theme of the following term paper, and it presents as research problem: How the relation between the trajectory of black adolescents and the socio-educational measures of restriction and deprivation of freedom, provided by the ECA [Child and Adolescent Statute], is set? Its general objective: to understand the relation between the trajectory of black adolescents and socio-educational measures of restriction and deprivation of freedom in order to contribute with the discussion on the topic and indicate possible alternatives. From the formulation of the leading questions: What were the living conditions of black adolescents during Brazil?s slavery period? Which were the state measures destined to adolescents between slavery abolition and ECA's enacting, and what is the prevalence of black adolescents in these measures? What were the achievements expected in the ECA and the limitations of socio-educational measures of restriction and deprivation of freedom given the focus on the race/color of black adolescents? To address the problem and carry out the research, it was used the dialectical-critical method based on the Critical Social Theory and with the categories: work, historicity, contradiction and mediation, which substantiates the understanding of the socio-historical formation of Brazil, life conditions and trajectory of black adolescents, state measures aimed at adolescents, and the advancements and limitations of the Child and Adolescent Statute. The research was developed using a mixed method approach, that is, quantitative and qualitative research, and through bibliographic and documentary research to collect data related to the theme. The source of documentary research that provided an approximation to the race/color profile of adolescents served by the socio-educational measures of restriction and deprivation of freedom provided by the ECA was the SINASE [National System of Socio-Educational Service] Annual Survey of years 2017 and 2023, expressing that the majority of these socio-educational users are black adolescents. In the year of 2023 the race/color category data from SINASE, corresponds to 63,8% for ?black?. After articulating the trajectory of the slavery period that marked the socio-historical formation of Brazil and the responses of repression and precarious social policies presented by the State. The conclusion was that this trajectory is directly related to the presented data. It was also concluded the need to expand studies on the topic. [resumo fornecido pelo autor]
Esta monografia tem como temática a trajetória dos adolescentes negros e as medidas socioeducativas de restrição e privação de liberdade e apresenta como problema de pesquisa: Como se dá a relação da trajetória dos adolescentes negros e das medidas socioeducativas de restrição e privação de liberdade previstas no ECA? Em seu objetivo geral: de compreender a relação entre a trajetória de adolescentes negros e as medidas socioeducativas de restrição e privação de liberdade, com vistas a contribuir com o debate desta temática e indicar possíveis alternativas. A partir da formulação das questões norteadoras: Quais as condições de vida dos adolescentes negros do período escravista no Brasil? Quais as medidas estatais destinadas aos adolescentes entre a abolição da escravatura e a promulgação do ECA e qual a prevalência dos adolescentes negros nestas medidas? Quais foram os avanços previstos no ECA e os limites das medidas socioeducativas de restrição e privação de liberdade a partir do recorte de raça/cor de adolescentes negros? Para responder ao problema e realizar a pesquisa, utilizamos o método dialético-crítico, embasado na Teoria Social Crítica e com as categorias: trabalho, historicidade, contradição, totalidade e mediação, as quais nos fundamentam na compreensão da formação sócio-histórica do Brasil, das condições de vida e trajetória dos adolescentes negros, das medidas estatais destinadas aos adolescentes e sobre os avanços e limites do Estatuto da Criança e do Adolescente. A pesquisa foi desenvolvida a partir da abordagem com enfoque misto, ou seja, da pesquisa quantitativa e qualitativa e através das pesquisas bibliográfica e documental para coleta de dados relacionados à temática. A fonte de pesquisa documental que proporcionou uma aproximação ao perfil raça/cor dos adolescentes atendidos pelas medidas socioeducativas de restrição e privação de liberdade previstas no ECA foi o Levantamento Anual do SINASE dos anos de 2017 e 2023, expressando que esses socioeducandos são em sua maioria adolescentes negros. No ano de 2023 os dados da categoria raça/cor do SINASE, corresponde à 63,8% para negros. Após analisar a trajetória do período escravista que marcou a formação sócio-histórica do Brasil e as respostas de repressão e políticas sociais precarizadas apresentadas pelo Estado. Concluímos que essa trajetória está diretamente relacionada com os dados apresentados. E ainda, pela necessidade de ampliação de estudos sobre a temática. [resumo fornecido pelo autor]
Keywords: Serviço social; Adolescentes negros; Medida socioeducativa; Brasil. [Estatuto da criança e do adolescente (1990)]; Brasil - História